2015
DOI: 10.1016/j.combustflame.2015.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Freely-propagating flames in aluminum dust clouds

Abstract: The free propagation of isobaric flames through aluminum dust clouds is investigated in an extensive series of experiments using two facilities with different scales. In small-scale laboratory experiments, spherical flame propagation occurs in aluminum dust clouds contained within 30-cm-diameter latex balloons, whereas in large-scale tests, flames propagate vertically through unconfined aluminum dust clouds with a vertical scale of about 4 m. The balloon experiments are performed with suspensions of aluminum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…While the burning velocity is a well-established concept that scales the turbulent flame speeds of gaseous and low-boilingpoint liquid fuels [116,126,127], it is not completely clear yet if this concept can be applied in the same way to metal-fuel flames of all scales and turbulence intensities. Our recent experiments have demonstrated that the flame speeds of both laboratory-scale metal flames, including stabilized and propagating flames, and largescale metal flames studied during field trials are indeed scalable using the burning velocity concept [128]. These promising results suggest that burning velocities of metal flames derived from laboratory experiments can be used as a first approximation in designing turbulent metal-fuel combustors required for transportation and industrial applications.…”
Section: Burning Velocities Of Metal-fuel Suspensionsmentioning
confidence: 94%
See 2 more Smart Citations
“…While the burning velocity is a well-established concept that scales the turbulent flame speeds of gaseous and low-boilingpoint liquid fuels [116,126,127], it is not completely clear yet if this concept can be applied in the same way to metal-fuel flames of all scales and turbulence intensities. Our recent experiments have demonstrated that the flame speeds of both laboratory-scale metal flames, including stabilized and propagating flames, and largescale metal flames studied during field trials are indeed scalable using the burning velocity concept [128]. These promising results suggest that burning velocities of metal flames derived from laboratory experiments can be used as a first approximation in designing turbulent metal-fuel combustors required for transportation and industrial applications.…”
Section: Burning Velocities Of Metal-fuel Suspensionsmentioning
confidence: 94%
“…Little data on the effect of turbulence on the flame speed of metal fuels is available [122], but our recent measurements show a large increase in burning rate for large-scale flames in field tests that contain some residual turbulence created during the required metal-fuel dispersal process [75,128]. Turbulent combustion of traditional fuels remains a challenging area of active research [126,127] and, therefore, much remains to be learned about turbulent metal flames.…”
Section: Controlling Particle Combustion Mode and Burning Rates Throumentioning
confidence: 96%
See 1 more Smart Citation
“…This situation is distinct from homogenous reactive media, as exemplified by gaseous mixtures, where fluctuations in concentration only occur on scales much smaller (e.g., mean molecular spacing) than the flame thickness, permitting a clear separation of scales by several orders of magnitude. In heterogeneous media (e.g., fuel particulates suspended in gaseous oxidizer [1,2] or mixtures of solid reactants as encountered in Self-propagating High-temperature Synthesis, SHS [3,4]), the scale of the heterogeneity can be comparable to or greater than the flame thickness, raising the question of how the statistical properties of the media influence the flame dynamics.…”
Section: A Flame Propagation In Random Mediamentioning
confidence: 99%
“…Even though this choice of kinetics is a qualitatively good description for such systems, Brailovsky et al [24] have shown more recently that ignition reaction kinetics and Lewis number. Thermo-diffusive instabilities for these systems in two forms of "Cells" for low Lewis number values (Le < 1), and "Oscillations" for high Lewis number values (Le > 1), have been observed in previous studies [20][21][22][23]. This paper studies the regime of rich metal particles in gas.…”
Section: Introductionmentioning
confidence: 96%